Is There a Relationship Between Cortisol and Treatment Response in Chronic Aphasia?. Issue 3 (July 2022) - Gravier, Michelle L.; Hula, William D.; Johnson, Jeffrey P.; Autenreith, Alyssa; Dickey, Michael Walsh
Abstract : Purpose: To evaluate whether levels of cortisol, a stress-related hormone, predicted response to intensive speech–language intervention for individuals with chronic aphasia (IWA). Secondary analyses explored baseline cortisol levels, change following intervention, association between cortisol levels and aphasia severity, self-reported communicative distress, and chronic stress. Method: Afternoon salivary cortisol levels were measured in 14 IWA during the first and last weeks of a 4-week intensive speech–language intervention epoch. Behavioral outcome measures were collected pre- and postintervention. Results: Cortisol levels did not significantly predict treatment response in this sample of IWA, although a positive trend was present. Baseline cortisol levels were not abnormally elevated, did not change from pre- to postintervention, and were not significantly correlated with any of the behavioral outcome measures. Discussion: Although afternoon salivary cortisol levels did not robustly predict treatment response in this participant sample, future studies may be warranted that include IWA with elevated levels of cortisol at pretreatment.